Direction of and selection criteria in cassava - Bueno, Álvaro (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was the evaluation of direction and efficiency of different selection criteria applied at the segregating generation in cassava (Manihot esculenta Crantz) crosses. The experiments were conducted at Centro Nacional de Pesquisa de Mandioca e Fruticultura, in Cruz das Almas, Bahia State, Brazil. Selection criteria used were weights of roots, aerial part and plant total, number of roots/plant and harvest index, which were applied in the positive and negative sense on seedling samples of five open pollinated families, in the crop year of 1983/84. Clones resulting from selection were evaluated in 1984/85, in randomized complete blocks, where the treatments were the selection criteria and replications the number of selected clones in each sample. Means and variances of samples were similar, therefore selection was not biased by the constitution of samples. Traits which were more affected by environmental variation were weights of roots, aerial part and plant total, and the most stable one was harvest index. In general, the positive selection was more efficient than the negative one, but selection of genotypes with high harvest index gave origin to clones with lower weights of aerial part and plant total. Positive selection for aerial part weight contributed for reduction of clone harvest index. For selection of clones with high root weight the most efficient criterion was total-plant weight, followed by aerial part weight, number of roots/plant, root weight and harvest index. It is suggested that the main criteria should be applied simultaneously, avoiding the use of isolated ones.